Weed Seed Bank Density in Seven-Year-Old Conservation in No-Till System - Haidar, Mustapha; Siblani, Walaa (Journal of Agricultural Studies, 2023)
Weed management remains a challenge when introducing new cropping systems. In Lebanon, farmers are increasingly adopting conservation agriculture (No-till) because it saves energy and reduces water and nutrient erosion. However, introducing a new system will cause a significant shift in production and management practices and is expected to produce novel weed management challenges. Thus, knowledge of soil seed banks of weeds in such systems is vital in designing effective weed management strategies. The objective of this research was to assess the size of the weed seed bank in seven-year-old conservation no-till fields. Soil samples were collected from established till and no-till fields at a depth of 0-5 cm. Transient and persistent weed seeds banks were evaluated. Results provide tangible evidence that the weed seed bank at a depth between 0-5cm in no-till system is greater than in till system. The no-till fields contained almost seven times the density of monocot and dicot weed seeds than in the conventional tilled fields. Ongoing work that builds on present results will help gain knowledge pertaining to weed seed bank dynamics in no-till system compared with conventionally tilled system.